Politics, Migration and Race. A Conversation with Yannis Hamilakis - Pintucci, Alessandro (Ex Novo: Journal of Archaeology, 2021)
Yannis Hamilakis is Joukowsky Family Professor of Archaeology and Professor of Modern Greek Studies at the Brown University (USA). His main research and teaching interests are the socio-politics of the past, the body and bodily senses, the archaeology of eating and drinking, the ontology and materiality of photography, archaeology and nationalism, archaeological ethnography, and critical pedagogy in archaeology. Yannis is committed to an anthropologically-informed, critical archaeological engagement with past and present material culture, and to the inter-disciplinary nature of archaeological work. This position recognises the historically contingent nature of archaeology as a device of western modernity, as well as its potential to enable a critical and reflexive experiential encounter with the material world. He also believes on a politically committed archaeological and academic practice, devoted to social justice.